Efektivitas model burjiu untuk mendukung ibadah haji dan umrah di era new normal - Hakim, Luqmanul; Muhyi, Muhammad; Hanafi, Muh.; Rangga Prastyana, Brahmin; Margisal Utomo, Gatot (Universitas Nusantara PGRI Kediri, 2022)
Fitness is very important for prospective Pilgrims and Pilgrims because fitness can do all activities on Hajj and Umrah, which is famously very heavy. Currently, there is no form of exercise that can improve the fitness of prospective Pilgrims and Umrah pilgrims. The purpose of the study was to determine the effectiveness of the Burjiu program (Bugar Jamaah Hajj and Umrah or Bugarkan Jasmanimu) to support improving physical fitness through movement activities designed to help pilgrims who will perform Hajj and Umrah from a physical perspective. The research method is quasi-experimental research using a pre-test, post-test randomized group design, namely a pre-test of physical fitness level, then carrying out the Burjiu program, which is practiced twice a week and followed by a post-test of fitness level using MFT. The sample of this study was as many as 22 men with an age range varying between 28 to 57 years. Data collection techniques use practice tests, and data analysis techniques use t-test. The results showed that through implementing the Burjiu program, there was no effect on increasing physical fitness in participants, with test results of 0.055 <0.05. The research concludes that the Bujiu program developed and tested in preparing physical conditions has not provided significant changes, so further studies are needed in this study.